Exploring EFL Students Difficulties and Strategies in Learning TOEFL ITP of Structure and Written Expression - Arif Bulan; M. Nur Imansyah; Nur Wahyuni; Lili Suryaningsih; Hasan Hasan (Universitas Hamzanwadi, 2023)
Nowadays the TOEFL test is very important. The TOEFL test is not only to measure English proficiency, but also for the sake of scholarship requirements, and as a requirement to graduate from college. This study explores the difficulties of EFL students in learning the TOEFL ITP of Structure and Written Expression (SWE) and how EFL students overcome difficulties in learning the TOEFL ITP of SWE. This study uses a narrative inquiry design. The data used in this study is qualitative data obtained from information provided by students through questionnaires and interviews. The results of the study show that there are several difficulties for students in learning TOEFL ITP, namely sentences with multiple clauses, sentences with inverted subjects and verbs, problems with prepositions, problems with the form of the verb, sentences with one clause, problems with subject/verb agreement. The way students overcome difficulties in the TOEFL ITP of SWE is to re-learn what has been taught by the tutor, reopen the module, learn from several other references besides the reference given by the tutor, learn from youtube, re-learn with classmates who have mastered the material. , do the practice questions independently. The findings in this research are expected to give an empirical contribution to TOEFL teachers to pay attention to students' difficulties in learning TOEFL ITP, especially SWE.